Fearing the "Turk" and Feeling the Spirit: Emotion and Conversion in the Early Modern Mediterranean. (25th May 2015) - Dursteler, Eric R
Abstract : The early modern period was an age of expansive religious refashioning and upheaval. In the Mediterranean this was the golden age of the renegade, as converts, particularly from Christianity to Islam, were termed. While fear was almost universally evoked in these cases, there is ample evidence of widespread voluntary conversion in the Mediterranean. Emphasising violence allowed converts, particularly those seeking reconciliation, to situate the locus of agency outside themselves and thus redirect blame to those responsible for their alleged mistreatment. Evoking fear and violence, whether true or not, was a socially acceptable way to justify conversion, was validated by inquisitors as an acceptable motivation for apostasy, and usually led to a quick reconciliation. There is no question that a certain degree of trepidation informed decisions to convert, but we should be cautious in accepting at face value repetitive claims of coercion. It is likely that many of the converts who attributed their conversions to coercion may in fact have been motivated by other factors, and only retrospectively evoked fear to mask their apostasy, or rather to make it more palatable, and to ease their re‐entry into their faith communities.